Structural DNA Nanotechnology - Seeman, Nadrian C. (Cambridge : Cambridge University Press, 2015)
Written by the founder of the field, this is the first text of its kind, providing a definitive introduction to structural DNA nanotechnology. Readers will learn everything there is to know about the subject from the unique perspective of the leading expert in the field. Topics covered range from origins and history, to design, experimental techniques, DNA nanomechanics devices, computing, and the uses of DNA nanotechnology in organising other materials. Clearly written, and benefiting from over 200 full colour illustrations, readers will find this an accessible and easy to follow text that is essential reading for anyone who wants to enter this rapidly growing field. Ideal for advanced undergraduate and graduate students, as well as researchers in a range of disciplines including nanotechnology, materials science, physics, biology, chemistry, computational science and engineering.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Nanobiotechnology; DNA -- Industrial applications; DNA -- Synthesis